Taxonomic Notes on Helicia (Proteaceae) I: Revision for Two Species from Continental Asia with new synonym and typification - Wang, Yuer (Phytotaxa, 2025)
As part of a revision of the genus Helicia (Proteaceae), the taxonomic history, type information, amended description, and updated distribution of two species with a distribution in the Northern Indo-Chinese floristic region, Helicia cauliflora and H. pyrrhobotrya, are presented. With evidence from recent collections, Helicia dongxingensis is reduced to a synonym of H. cauliflora, and the synonym status of H. petelotii to H. pyrrhobotrya that was proposed earlier by C.Y.Wu is hereby reinstated.